PSYCHOLOGICAL STRESS AND CANCER PROGRESSION - Agnieszka Kwiatkowska,; Konrad Strużek,; Ewelina Mączka,; Wiktor Tracz,; Patrycja Świercz,; Kinga Teper,; Sandra Khiralla-Gawlik,; Aleksandra Anna Strzelecka,; Aleksandra Ewa Basak, (International Journal of Innovative Technologies in Social Science, 2025)
Background: Psychological stress, particularly in its chronic form, is increasingly recognized as a factor influencing cancer progression through complex neuroendocrine, immunological, and molecular mechanisms. Chronic activation of the hypothalamic-pituitary-adrenal (HPA) axis and the sympathetic nervous system (SNS) leads to dysregulated cortisol and catecholamine levels, which suppress anti-tumour immunity, promote angiogenesis, and enhance tumour cell invasiveness and metastasis.Aim: To synthesise current evidence on the biological mechanisms linking psychological stress to cancer progression and to highlight the therapeutic potential of psychosocial interventions in oncology.Material and methods: A narrative literature review was conducted using the PubMed database. Relevant preclinical and clinical studies published between 2000 and 2024 were selected to examine the influence of psychological stress on cancer biology and disease progression.Results: Chronic stress contributes to cancer growth, metastasis, and therapy resistance through hormonal imbalance, immune suppression, and chronic inflammation. Disruption of the tumour microenvironment further facilitates malignant progression. Studies particularly emphasize these effects in breast and ovarian cancers. Psychosocial interventions such as cognitive behavioural therapy (CBT) and mindfulness-based stress reduction (MBSR) have demonstrated benefits in both psychological well-being and biological markers of disease activity.Conclusions: Psychological stress significantly impacts cancer progression through multiple biological pathways. Integrating stress-reducing interventions into standard oncological care may enhance patient outcomes and offer a complementary strategy in cancer management.